Организация внутреннего аудита операций между связанными сторонами в корпоративных образованиях (Путеводитель предпринимателя)
In the article the author’s position on certain aspects of internal audit of transactions between related parties within the framework of the transformation of the management of large associations in Russia and in accordance with the IFRS financial statements for the formation.